Prevalence, clinical features and treatment outcomes of patients with myasthenia gravis positive for antibodies to muscle-specific kinase in Thailand. - Witoonpanich, R; Dejthevaporn, C; Pulkes, T; Tunlayadechanont, S; Boonkongchuen, P; Pongpakdee, S; Vincent, A (2013)
A small but variable subgroup of patients with myasthenia gravis (MG) who have antibodies to muscle-specific kinase (MuSKAb-MG) can present with distinct phenotypes and are often treatment-resistant. The prevalence, clinical phenotypes and outcomes of treatment of patients with MuSKAb-MG in Thailand were determined. Eight (16.3%) of the 49 patients with generalized MG who were negative for acetylcholine receptor antibodies (AChRAb) were positive for muscle-specific kinase antibodies. Most patients had predominant oculobulbar features and respiratory failure occurred in three. At follow up, three out of the seven patients who underwent thymectomy were in complete stable remission and four had improved and were on reduced immunosuppression medication, suggesting a possible benefit of thymectomy.